1995
DOI: 10.1099/0022-1317-76-9-2257
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence of a cucumber mosaic virus from Ixora that is deficient in the replication of satellite RNAs

Abstract: A cucumber mosaic virus (CMV-Ix) from Ixora is unusual in that it does not support the accumulation of some well-characterized CMV satellite RNAs in plants. CMV-Ix can support a particular satellite RNA variant which causes lethal tomato necrosis when inoculated with other CMV strains but not when inoculated with CMV-Ix. This difference in ability to support accumulation of specific satellite variants is apparent even when their sequences differ by only 10 nucleotides. Electroporation of tomato protoplasts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
(50 reference statements)
1
14
1
Order By: Relevance
“…presence of conserved TG tract in 5 0 UTR (as reported earlier by Boccard and Baulcombe [1], the motif 'CAA CAG TCC TC' and GGT TCA ATT CC in the 3a and IR gene, respectively and a highly conserved region 'TCC AGC TTA CGG CTA AAA TGG TCA GTC G' in 3 0 UTR, like in other strains of CMV strains was also obtained [10]. However, no substitutions were observed in 5 0 UTR and IR regions.…”
supporting
confidence: 81%
“…presence of conserved TG tract in 5 0 UTR (as reported earlier by Boccard and Baulcombe [1], the motif 'CAA CAG TCC TC' and GGT TCA ATT CC in the 3a and IR gene, respectively and a highly conserved region 'TCC AGC TTA CGG CTA AAA TGG TCA GTC G' in 3 0 UTR, like in other strains of CMV strains was also obtained [10]. However, no substitutions were observed in 5 0 UTR and IR regions.…”
supporting
confidence: 81%
“…7 a). Although the similarity scores for cucumovirus 3a proteins recently reported by McGarvey et al (1995) showed sequence relationships among the cucumoviruses comparable to those deduced in the present study, they were generally lower in magnitude. The higher values obtained in our study may be explained by the fact that we employed the GAP program, which considers all possible alignments and gap positions and creates the alignment of two complete sequences with the largest number of matched bases and the fewest gaps ; the similarity scores calculated by McGarvey et al (1995) were based on global alignments of multiple sequences using the CLUSTAL algorithm with fixed gap positions.…”
Section: Characterization Of the Psv 3a Protein And Comparison With Ocontrasting
confidence: 42%
“…Like other cucumoviruses, the 3h UTRs of PSV-W and PSV-ER RNA3s contain the 40 nt sequence domain conserved in all cucumovirus RNAs so far examined (Figs 3 and 4, underlined). This highly conserved sequence, which is important for RNA3 accumulation (Boccard & Baulcombe, 1993 ;McGarvey et al, 1995), may be exploited in designing universal probes for the detection and diagnosis of cucumovirus infections and also in designing universal primers for cDNA synthesis and cloning of cucumovirus RNAs. It is of interest to note that the only known variant nucleotide (arrowhead above sequence in the 3h UTR, Figs 3 and 4) in this highly conserved 40 nt sequence (McGarvey et al, 1995) is different for each of the three PSV strains : G for strain W, U for strain ER and A for strain J.…”
Section: Comparative Nucleotide Sequence Analysis Of Rna3 From Psv Stmentioning
confidence: 99%
“…The 5 UTR of PSV RNA3, like those of all other cucumoviruses, contains the conserved UG tract (5 GUGUUGUUGUUGGU3 ) that is required for efficient accumulation of RNA3 [1]. Like other members of the genus Cucumovirus, the 3 UTRs of RNA1, 2 and 3 of PSV-Mi are highly conserved and contain a 40 nt sequence (5 GATCGGGTTGTCCATCCAGCTAACGGCTAAAATGGTCAGT3 ) conserved in all Cucumovirus RNAs, which is also important for RNA accumulation [10]. Among the UTR's, the 5 UTRs of RNA1 and 2 of all PSV strains are most conserved as the 5 UTR of PSV-Mi RNA1 and 2 were 83.5 ∼ 96.1% identical to those of the PSV-ER and W strains whereas the 5 UTR of RNA3 had only 78.4 ∼ 79.8% identity with the 5 UTR of RNA3 to PSV-ER and W (PSV-ER and -W share over 90% identity in this region).…”
mentioning
confidence: 99%